The relationship between midwife communication and the level of satisfaction of pregnant women in antenatal care services at the UPTD Kotanopan Health Center, Mandailing Natal Regency, North Sumatra Province in 2024. - Sinaga, Kamelia; Simbolon, Rolasnih Lilista; Manurung, Herna Rinayanti; Bakara, Srimuliani Putri; Sianturi, Nova Cristiana; Niska, Rinny (Institute of Computer Science (IOCS), 2024)
World Health Organization (WHO) data on national health status in achieving the Sustainable Development Goals (SDGs) targets states that globally around 830 women die every day due to complications during pregnancy and childbirth, with an MMR of 216 per 100,000 live births (WHO, 2019) As many as 99 percent of maternal deaths due to pregnancy, childbirth or birth problems occur in developing countries. The MMR ratio is still considered quite high as targeted to be 70 per 100,000 live births in 2030 (WHO, 2019). WHO estimates that more than 585,000 mothers die each year during pregnancy or childbirth. Research Objectives The Relationship Between Effective Midwife Communication and the Level of Satisfaction with Antenatalcare Services in Pregnant Women at the Kotanopan Health Center UPTD, Mandailing Natal Regency, North Sumatra Province in 2024. Quantitative research method using a Cross Sectional approach. This study uses an extensive dataset to see many cases and relationships between variables. The results of the study showed a significant relationship between midwife attitudes (P value = 0.000 <α value = 0.05) and midwife communication (P value = 0.000 <α value = 0.05) with satisfaction with antenatal care services for pregnant women at the Community Health Center